Growth traits of the Dorper sheep. II. Genetic and phenotypic parameters - Inyangala, B.A.O.; Rege, J.E.O.; Itulya, S. (1992)
Data on 969 lambs collected over a 10-year period (1978 to 1987) on Dorper sheep at Ol'Magogo were used in this study. Lamb traits studied were weights from birth to yearling and absolute growth rates between adjacent stages of growth. Heritability estimates from paternal half-sib analysis were: 0.15±0.07, 0.18±0.08, 0.39±0.11, 0.55±0.13, 0.53±0.13, 0.14±0.07, 0.28±0.09, 0.59±0.14, 0.49±0.12 and 0.49±0.12; for birthweight (BIRTHW), adjusted weaning weight (ADJWWT), adjusted six-months weight (ADJSMW), adjusted nine-months weight (ADJNMW), adjusted 12-months weight (ADJTMW), pre-weaning growth rate (GR1), weaning to six months (GR2), six to nine months (GR3), nine to 12 months (GR4), and birth to yearling (OVRGRT), respectively. Post-weaning heritability estimates were generally higher than those for pre-weaning suggesting a lower direct genetic influence early in life. Genetic and phenotypic correlations estimated between weights were mainly positive (0.15 to 0.99 and 0.02 to 0.98, respectively). There were generally high genetic and phenotypic correlations between adjacent weights, between weights and rates of growth, and among growth rates themselves.